Reactivity of Horse Sera to Antigens Derived From Sarcocystis falcatula–Like and Sarcocystis neurona - Borges-Silva, Waléria; de Jesus, Rogério F.; Ferreira, Rachel; Gondim, Luís F. P. (Frontiers in Veterinary Science, 2020)
Sarcocystis neurona and Sarcocystis falcatula are protozoan parasites endemic to the Americas. The former is the major cause of equine protozoal myeloencephalitis (EPM), and the latter is associated with pulmonary sarcocystosis in birds. The opossum Didelphis virginiana is the definitive host of these parasites in North America. Four Didelphis spp. are found in Brazil, and in most reports in this country, Sarcocystis spp. shed by opossums have been classified as Sarcocystis falcatula-like. It is unknown whether reports on S. neurona-seropositive horses in Brazil are also derived from exposure of horses to S. falcatula-like. The aim of this study was to test sera reactivity of 409 horses in Brazil using antigens derived from a Brazilian strain of S. falcatula-like (Sarco-BA1) and from a North American strain of S. neurona (SN138). Samples were examined by imunofluorescent antibody tests (IFAT) at start dilutions of 1:20, and a selected number of samples was tested by Western blot. Sera from 43/409 (10.5%) horses were reactive to S. falcatula-like and 70/409 (17.1%) were reactive to S. neurona antigen Sera from 25 (6.1%) animals were positive for both parasites by IFAT. A poor agreement was observed between the two employed IFATs (Kappa = 0.364), indicating that horses were exposed to more than one Sarcocystis species. Horse sera evaluated by WB consisted of four sera reactive to S. falcatula-like by IFAT, six sera positive to S. neurona by IFAT, two sera that tested negative to both parasites by IFAT, and a negative control horse serum from New Zealand. Proteins in the range of 16 and 30 KDa were recognized by part of IFAT-positive sera using both antigen preparations. We concluded that Brazilian horses are exposed to distinct Sarcocystis spp. that generate different serological responses in exposed animals. Antigens in the range of 16 and 30 KDa are probably homologous in the two parasites. Exposure of the tested horses to other Sarcocystis spp., such as S. lindsayi, S. speeri and S. fayeri or S. bertrami cannot be excluded in the current study.